Evaluasi Titer Antibodi Sebelum Dan Sesudah Vaksinasi Septicaemia Epizootica Pada Sapi Bali Di Desa Oebelo, Kecamatan Kupang Tengah, Kabupaten Kupang - Rizaldo Mariano Ludji; Yohanes T.R.M.R Simarmata; Maxs U.E Sanam (Jurnal Veteriner Nusantara, 2022)
Septicemia epizootica is an infectious disease found in ruminants. One way to control and overcome Septicemia epizootica disease is through vaccination. This study aims to determine antibody titers before and after vaccination of Septicaemia epizootica in bali cattle in Oebelo village, Central Kupang district, Kupang district. Blood serum was taken before and after vaccination on 20 cows, then an indirect ELISA test was performed to see the antibody titer value. The relationship between antibody titer values before and after vaccination according to statistical data analysis using SPSS 2016 is the average antibody titer value before vaccination is 58.95 EU and the antibody titer value after vaccination is 101.30 EU. for a significant value (P<0.05) the antibody titer value before vaccination against after vaccination with a P value of 0,003, it showed that there was a significant difference between the titer value before and after vaccination.